Human DUX4 and mouse Dux interact with STAT1 and broadly inhibit interferon-stimulated gene induction - Spens, Amy E; Sutliff, Nicholas A; Bennett, Sean R; Campbell, Amy E; Tapscott, Stephen J (eLife, 2023)
DUX4 activates the first wave of zygotic gene expression in the early embryo. Mis-expression of DUX4 in skeletal muscle causes facioscapulohumeral dystrophy (FSHD), whereas expression in cancers suppresses IFNγ induction of major histocompatibility complex class I (MHC class I) and contributes to immune evasion. We show that the DUX4 protein interacts with STAT1 and broadly suppresses expression of IFNγ-stimulated genes by decreasing bound STAT1 and Pol-II recruitment. Transcriptional suppression of interferon-stimulated genes (ISGs) requires conserved (L)LxxL(L) motifs in the carboxyterminal region of DUX4 and phosphorylation of STAT1 Y701 enhances interaction with DUX4. Consistent with these findings, expression of endogenous DUX4 in FSHD muscle cells and the CIC-DUX4 fusion containing the DUX4 CTD in a sarcoma cell line inhibit IFNγ induction of ISGs. Mouse Dux similarly interacted with STAT1 and suppressed IFNγ induction of ISGs. These findings identify an evolved role of the DUXC family in modulating immune signaling pathways with implications for development, cancers, and FSHD.
Keywords: DUX4; DUX; DUXC; STAT1; interferons; interferon stimulated genes; interferon-gamma